Evaluation of Sargassum fluitans extract as liquid organic fertilizer to improve vegetative growth of Inpari 32 Rice on saline soil - Sri Wahyuni Basoka; Eko Aprianto Johan; Rian Arini; Fitriah Amir (Anjoro: International Journal of Agriculture and Business, 2025)
This study aims to evaluate the potential of S. fluitans bioalgae extract as a liquid organic fertilizer to enhance the vegetative growth of Inpari 32 Rice in saline soils in Southeast Sulawesi. The research was conducted at the Phytopathology Laboratory and Experimental Garden of the Faculty of Agriculture, Halu Oleo University. The study was carried out from February to May 2025. The research used a randomized block design (RBD) with four treatment concentrations, each repeated 3 times as groups. The experiment was conducted by applying S. fluitans at the following concentrations: P0 = 0%, P1 = 10%, P2 = 20%, and P3 = 30%. The variables observed included plant height, leaf number, and clump number. If there was a significant effect in the analysis of variance, the least significant difference (LSD) test was performed at a significance level of α = 0,05. The results showed that the application of S. fluitans significantly increased all growth parameters compared with the control. The 10% concentration produced the highest plant height, while the 20% concentration produced the highest number of leaves. An increase in the number of tillers was also observed across all S. fluitans treatments. These findings indicate that S. fluitans contains bioactive compounds that stimulate rice vegetative growth. The optimal concentration variation for different parameters shows the complexity of the dose response and the need for further optimization. This study concludes that S. fluitans has the potential to serve as a sustainable organic fertilizer alternative to increase rice productivity in saline soils of Southeast Sulawesi, contributing to food security and environmentally friendly agriculture.